1,8-Diazabicyclo[6.6.6]eicosa-4,11,17-triyne: a flexible cage for protons, copper(I) and silver(I) - Kunze, Andreas; Gleiter, Rolf; Rominger, Frank (Chemical communications, 1999)
X-Ray structure analysis of the diprotonated cage of 3 and its silver(I) and copper(I) complexes reveals in all three cases the in,in conformation and a significant shortening of the intrabridgehead distance from 5.05 Å in 3 to 4.85 Å for 3·2H+, 4.23 Å for 3·Cu+ and 4.61 Å for 3·Ag+.